2022
DOI: 10.1038/s41598-022-23300-y
|View full text |Cite
|
Sign up to set email alerts
|

Sportomics method to assess acute phase proteins in Olympic level athletes using dried blood spots and multiplex assay

Abstract: Sportomics is a subject-centered holistic method similar to metabolomics focusing on sports as the metabolic challenge. Dried blood spot is emerging as a technique due to its simplicity and reproducibility. In addition, mass spectrometry and integrative computational biology enhance our ability to understand exercise-induced modifications. We studied inflammatory blood proteins (Alpha-1-acid glycoprotein—A1AG1; Albumin; Cystatin C; C-reactive protein—CRP; Hemoglobin—HBA; Haptoglobin—HPT; Insulin-like growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, several studies have shown a correlation between high-intensity/-volume exercise and arterial calcification [ 25 ]. Additionally, (i) marathon runners experience NLRP3 inflammasome-related vascular inflammation [ 26 ], in which UCP1 expression may play a role [ 27 ], and (ii) a strong correlation between the upregulation of acute phase proteins and performing world-class/Olympic sports has been found [ 28 ]. These findings may contribute to a potential explanation for a higher prevalence of arterial calcification in elite athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies have shown a correlation between high-intensity/-volume exercise and arterial calcification [ 25 ]. Additionally, (i) marathon runners experience NLRP3 inflammasome-related vascular inflammation [ 26 ], in which UCP1 expression may play a role [ 27 ], and (ii) a strong correlation between the upregulation of acute phase proteins and performing world-class/Olympic sports has been found [ 28 ]. These findings may contribute to a potential explanation for a higher prevalence of arterial calcification in elite athletes.…”
Section: Discussionmentioning
confidence: 99%
“…A similar clinical and identical analytical approach is described by Bassani et al. [36] who studied 11 inflammatory blood proteins in almost 100 athletes over 16 different sports. The clinical similarity in these studies is that longitudinal DBS is carried out to monitor rather general proteins to get insight into the biochemical processes of both patients and athletes.…”
Section: Targeted Protein Determination With Clinical Applicationsmentioning
confidence: 98%
“…Additionally, they present a way to perform normalization for variations in the volume caused by the hematocrit (Hct) effect: through measurement of five proteins (albumin, C3, IgM, plasminogen and hemopexin) a scaling factor is introduced which allows internal normalization of the DBS amount [40]. A similar clinical and identical analytical approach is described by Bassani et al [36] who studied 11 inflammatory blood proteins in almost 100 athletes over 16 different sports.…”
Section: Targeted Protein Determination With Affinity Clean-upmentioning
confidence: 99%
“…In addition, a correlation was suggested between the reduction in TLR4 (Toll-like receptor 4) and the protective effect of exercise in heart diseases. A total of 1500 protein–protein interactions were highlighted in this study and 30 of the 44 core proteins were associated with immune system processing [ 101 ].…”
Section: Microsampling Applications Monitoring Lipids and Metabolitesmentioning
confidence: 99%